Phenological Stage Application of Gibberellin to Enhance Fruit Quality of Melon (Cucumis melo ‘Fujisawa’) under NFT Hydroponic System - Hidayat, Ramdan; Fasya, Elfira Rizki Oktaviana; Nugrahani, Pangesti; Zakiyah, Nur Meili (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
National melon production remains suboptimal due to the crop’s sensitivity to the environment and lack of management practices. This study analyzed the interaction between GA₃ concentration (0, 50, 100, 150 ppm) and application timing (pre-anthesis, anthesis, post-anthesis) on growth, yield, and fruit quality of Fujisawa melon in an NFT hydroponic system. Significant concentration × timing interactions (p<0.05) optimized fruit traits at 100 ppm + anthesis: weight increased by 0.49 kg (24.1%) to 2.03 kg, flesh thickness by 1.33 cm (25.7%) to 5.17 cm, diameter by 1.79 cm (10.9%) to 16.38 cm, and volume by 413 cm³ (21.2%) to 1,950 cm³ vs. control. Regardless of timing, 100 ppm GA₃ accelerated flowering (2.71 days) and harvest (3.87 days) vs. control and increased total soluble solids by 2.33 to 16.33ºBrix. Pre-anthesis application enhanced plant length by 8.57–9.41 cm and hastened flowering by 0.87–0.99 days compared to other timings. Leaf number and fruit cavity were unaffected by either treatment (p>0.05). The regression for fruit traits at anthesis (R²=0.74–0.85) confirmed optimum concentrations of 67.50–138.50 ppm; ≥150 ppm diminished benefits. These findings provide recommendations: 100 ppm GA₃ at anthesis maximizes yield components, 75 ppm at flexible times increases sweetness levels.